2009
DOI: 10.1080/13504850601018312
|View full text |Cite
|
Sign up to set email alerts
|

Foreign aid and ecological outcomes in poorer countries: an empirical analysis

Abstract: This article examines the relationship between foreign aid and ecological harm in developing countries. The study covers three types of ecological injury: carbon dioxide damage, water pollution and net deforestation. Results based on an empirical model where aid and injury are jointly determined, suggest that aid flows affect ecological conditions in poorer countries as well as being the result of these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Research on aid has also identified a number of other factors that may be correlated with aid allocations in developing countries, chief among them democratic conditions (for example, Arvin and Barillas, 2002;Knack, 2004) and the state of the environment (for example, Arvin et al, 2006;Arvin and Lew, 2009a). As is evident from this discussion, donors give aid for a variety of reasons that reflect both RN and DI.…”
Section: The Aid Literaturementioning
confidence: 90%
“…Research on aid has also identified a number of other factors that may be correlated with aid allocations in developing countries, chief among them democratic conditions (for example, Arvin and Barillas, 2002;Knack, 2004) and the state of the environment (for example, Arvin et al, 2006;Arvin and Lew, 2009a). As is evident from this discussion, donors give aid for a variety of reasons that reflect both RN and DI.…”
Section: The Aid Literaturementioning
confidence: 90%
“…The literature is inconclusive on this subject: While some suggest a negative relationship between aid and environmental protection, others argue that aid supports environmental protection. There are few empirical tests conducted on this subject, and the results are mixed (Arvin and Lew 2009). We suggest that this inconclusiveness arises when scholars ignore how the effect of aid is conditioned by alternative resource inflows from abroad.…”
Section: Introductionmentioning
confidence: 68%
“…Most studies have assessed the effects of environmental aid on specific environmental projects (Ross 1996), a specific country recipient (Gutner 2002), or even a specific donor agency (Dauvergne 2001). When it comes to an analysis of a broader set of countries, Arvin and Lew (2009) are the rare exception. They study the relationship between foreign aid and three ecological indicators in developing countries (CO 2 emissions, water pollution, and deforestation), and find that while foreign aid reduces CO 2 emissions, it increases water pollution and deforestation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Examples of programs, financed by United Nations, criticized for their environmental damage are the dams in Sardar Sarovar (India) and Pak Mun (Thailand), the development scheme in Polonoroeste (Brazil) or the mines in Singrauli (India). Besides, Arvin and Lew () find that donors are sending mixed signals to recipient countries through their aid policies; for example, by rewarding them for the preservation of their forest but not for the reduction of their CO 2 emissions.…”
mentioning
confidence: 99%